Evaluation of modified Dubois model for estimating surface soil moisture using dual polarization RISAT-1 C-band SAR data. Issue 13 (9th August 2021) - Dave, Rucha; Kumar, Gaurav; Kr. Pandey, Dharmendra; Khan, Armugha; Bhattacharya, Bimal
Abstract: The present study focuses on the soil moisture estimation using dual polarimetric RISAT-1, C-band SAR data in HH and HV polarization. The semi empirical approach derived by Dubois and the same modified and proposed as modified Dubois model (MDM) is worked for winter wheat crop from initial vegetative to maturity stage. Surface roughness model derived roughness is replaced with 's' parameter for retrieval of dielectric constant which is further used in Topp's model to derive soil moisture. Model derived soil moisture and ground measured soil moisture demonstrates pragmatic correlation after performing linear regression. The behaviour of inversion model varies at different crop stages depending on the soil exposure and crop cover. Normalized difference vegetation index from moderate resolution imaging spectroradiometer has also been evaluated to monitor crop status. Performance of MDM is promising for early and maturity stages of crop for soil moisture estimation.